Concept of a spectrometer for resonant inelastic X-ray scattering with parallel detection in incoming and outgoing photon energies - Strocov, V N (Journal of synchrotron radiation, 2010)
A spectrometer for resonant inelastic X-ray scattering (RIXS) is proposed where imaging and dispersion actions in two orthogonal planes are combined to deliver a full two-dimensional map of RIXS intensity in one shot with parallel detection at incoming hv(in) and outgoing hv(out) photon energies. Preliminary ray-tracing simulations with a typical undulator beamline demonstrate a resolving power well above 11000 with both hv(in) and hv(out) near 930 eV, with a vast potential for improvement. Combining this instrument - nicknamed hv(2) spectrometer - with an X-ray free-electron laser source simplifies its technical implementation and enables efficient time-resolved RIXS experiments